Investigating Perceptions on Gender Diversity and Inclusion in the Workplace: A Case Study on the Banking Sector in Egypt - Melek, Lidia (AUC Knowledge Fountain, 2024)
This thesis aims at providing an understanding of the perceptions of middle and senior managers on gender diversity and inclusion in the sector, and more importantly the factors leading to those perceptions. The main research question is: What are the perceptions of middle and senior level banking sector employees on gender diversity and inclusion in the sector? The researcher used a qualitative approach. A total of 13 semi-structured interviews were conducted, 10 interviews with middle and senior managers in the banking sector and 3 interviews with HR managers or directors in the sector. The analysis demonstrates organizational culture as a factor shaping perceptions through showing cultural differences between different types of banks. In line with social identity theory and stereotype threat theory, stereotypes emerged as another factor, these included: women being emotional, toxic managers, and fit for certain roles in the sector. The role of women as caretakers was also a factor which led to discussions around cost effectiveness of hiring women, as well as maternity leave and mid-career gaps. Finally, through feminist institutionalism lens the researcher analyzed policies related to gender diversity and inclusion and perceptions of them which were also a contributing factor. There is a limited understanding of gender diversity and inclusion where interviewees perceive the notion through representation lens rather than an empowerment one. Based on these findings, it is recommended that the way forward should be addressing those factors. To change perceptions and gender norms, it is suggested that a business case should be built for employers to drive gender inclusion in their respective organizations through proving its economic yield. Moreover, maternity leave policy as existing policy might unintentionally hinder women’s careers. Finally, real behavioral change is important to establish a true understanding of gender diversity and inclusion.